Effect of pH on chromaticity and colour stability of Curcumin and PLA-curcumin coating - Mohd Latiff, Nur Hanie; Abu Bakar, Ainaa Eliah; Othman, Rashidi; Mohd Hatta, Farah Ayuni; Ramya, Razanah; Wan Sulaiman, Wan Syibrah Hanisah (2021)
Understanding the limitations and unfavorable conditions of curcumin would be an advantage to increase the stability of the pigment. Therefore, the ultimate objective of this research is to evaluate the effects of pH on chromaticity and stability of curcumin and PLA-curcumin extracted from Curcuma longa (turmeric), as a potential natural source for coating. Curcumin is the major component in Curcuma longa that is responsible for its biological actions. The bright yellow extract from the turmeric comes from fat-soluble, polyphenolic pigments which is known as curcuminoids. Overall, the dark condition was preferable and stable for the curcumin brightness and slower the degradation percentage. Dark condition exhibited a better and stable colour degradation (approximately 40%) in all curcumin concentrations (1 mg/ml, 2 mg/ml and 3 mg/ml) as compared to light condition with 89.92%, 85.79% and 60.90%, respectively. PLA alone showed the highest chroma (C*) value at 3.08% in dark condition, which was slightly higher than in light condition (2.87%). The highest C* values were achieved in curcumin set with lower pH (pH 3, 5 and 7) and the lowest at higher pH (pH 9 and 11) in both light and dark conditions. However, all PLA-curcumin showed colour stability in both acidic (pH 3 and 5) and basic (pH 9 and 11) in dark condition only.